Insulin Resistance Mediates the Association Between Vitamin D and Non-Alcoholic Fatty Liver Disease - Caiyan Zou; Xuekui Liu; Maosheng He; Yan Sun; Yiquan Sang; Gangshan Peng; Yamei Ma; Houfa Geng; Jun Liang (International Journal of Preventive Medicine)
Background: Vitamin D (VD) deficiency and insulin resistance (IR) increase the risk of non-alcoholic fatty liver disease (NAFLD), but few studies have explored the potential mechanisms by which IR mediates the association between VD and the pathogenesis of NAFLD at the genetic level using publicly available databases. Methods: This is a cross-sectional study, and we utilized the National Health and Nutrition Examination Survey (NHANES) dataset, as well as data from GSE200765 obtained from the Gene Expression Omnibus (GEO) website. A total of 723 individuals who had completed liver ultrasound examination and the detection of VD levels were included in the final analysis. A gene expression dataset, GSE200765, was also downloaded from the GEO website, to explore the potential mechanism of VD and NAFLD. Results: In the NHANES data, covariates significantly differed in four VD categories, and the controlled attenuation parameter (CAP), vibration-controlled transient elastography-liver stiffness measurement (VCTE-LSM), and IR were reduced with an increase in VD levels. Mediation analysis revealed that IR mediated the association between VD and both CAP and LSM, and the estimated mediation effects were 29.0% and 39.8%, respectively. Bioinformatics analysis showed that seven differentially expressed genes (DEGs) (solute carrier family 2 member 2 [SLC2A2], protein phosphatase 1 regulatory subunit 3E [PPP1R3E], CAMP responsive element binding protein 3-like 3 [CREB3L3], Interleukin-6 [IL-6], peroxisome proliferator-activated receptor gamma coactivator 1-alpha [PPARGC1A], nuclear factor kappa B inhibitor alpha [NFKBIA], and phosphoenolpyruvate carboxykinase 2 [PCK2]) were enriched in the IR pathway in comparison groups (VD group vs. lipid group), suggesting that VD improved NAFLD via changed IR. Conclusions: VD deficiency and IR were the risk factors for NAFLD, and increased VD levels improved the status of NAFLD. The underlying mechanism may be that elevated VD levels reduced IR, which improved the expression of DEGs involved in the IR pathway.